Caribbean delight : moving beyond the sustainability discourse in tourism - Roessingh, Carel (2008)
Uses empirical data from Belize and the Dominican Republic to move beyond the dominant, sustainability discourse in the field of tourism, in which mass-tourism is per definition 'bad' and small-scale tourism is 'good' to gain an insight into what is actually going on at the micro level.